Animal welfare and productivity of laying hens housed in a cage-free floor system in the Capital Department of La Pampa: (Ingeniería Agronómica) (Semiárida, 2022)
In Argentina, poultry farms have been growing rapidly. The increase in the bird population and, especially, egg production has caused farms to become more technical and seek greater profitability in small spaces, to the detriment of the well-being of these animals. The concept of animal welfare (AB) was established, at the beginning, within parameters of a very broad nature and unscientific aspects, becoming an issue that was difficult to accept by producing countries. In fact, defining BA accurately and precisely, so that it is universally understood and approved, is an almost impossible task. Measuring it is equally difficult, because it is not known what the real demands are for the animal to satisfy the ideal behavioral and physiological conditions. Egg production in cage-free floor systems is diametrically different from confinement production. This is evident, above all, in the batteries of cages in buildings populated by thousands of birds in high densities, not only in management issues, but also in health and animal behavior aspects. Even so, floor systems maintain high production standards, little different from confined systems. The productive and BA evaluation was carried out on the former Fundación Nuestros Pibes farm (Coordinates 36° 37' 13' S and 64° 17' 26' W, altitude 200 meters above sea level), currently a company owned by Ecohuevos Pampa S.A.S. (Simplified Joint Stock Company), located in the peri-urban region of the city of Santa Rosa, La Pampa. The purpose of this final graduation project was to determine if a productive system of cage-free floor layers, located in the Capital Department of the province of La Pampa, reaches the productive standards established by the Hy-Line program in its management guides. , in order to establish it as a comparative advantage, as it is a system with a high BA status, in contrast to the productive results of traditional cage systems. In this work, the factors related to the cage-free production system were studied, comparing its results with those of conventional cage production methods, registered in the hybrid management guide. For freedom from hunger and thirst, the following indicators were evaluated: growth (live weight), feed consumption, egg production throughout lay and feed conversion efficiency. Regarding freedom from discomfort, the indicators were: animal density, temperature, relative humidity, air flow and light intensity; for freedom from pain, injuries and diseases, the following were evaluated: body condition, plumage status, degree of plumage dirtiness, presence of wounds and injuries, nail length and mortality; For the freedom to express normal behaviors and fear and stress, it was determined: absence of 4 abnormal behaviors such as bird exhaustion, cannibalism, and fear reaction test. The productive indicators of live weight at 18 weeks, feed consumption and feed conversion were acceptable for floor production. Only the percentage of laying was relatively lower (5%) than in confined birds, settling in the order of 85 - 90% at the peak of laying and maintaining it during the laying cycle. The daily quantity of eggs produced per housed bird was adequate, although this genetic line at the bottom reaches 0.93 egg.day-1.bird-1. It can be assumed that in floor systems there are losses of eggs due to breakage, when hens lay on the floor due to occupied nest boxes. In this experience, it was difficult to adapt the hens to laying in the nesting boxes, especially because they were not initially suitable for conditions of certain intimacy, which the hen requires at the time of laying. This meant that 50% of the eggs were collected from the floor. The situation involved protecting the nests with black nylon to darken them and placing blind floors with shavings in the nest boxes. This only solved 30% of the problem, with the habit of laying on the floor prevailing, an aspect that complicated collection and increased egg breakage. The welfare of production animals needs to be raised as a challenge to conquer and maintain markets. This was categorical in the present study since the floor hens had productive behaviors similar to those of caged hens, but they did not show stress, they had an absence of prolapses, cannibalism and they maintained healthy and clean plumage until the moment of molting. . The scientific community has been becoming more aware of this fact, especially in recent years, when consumer markets have begun to value ethics in animal production. Work of this type is essential to enable production techniques that provide greater comfort.
Keywords: chickens